Konseling Individu dengan Teknik Role Play untuk Mengatasi Perilaku Agresif Anak - Ratmi Sri Utami; Suryati Suryati (Journal of Society Counseling, 2025)
This study, titled "Individual Counseling with Role Play Techniques to Overcome Children's Aggressive Behavior," aims to identify, describe, and evaluate the effectiveness of individual counseling using role play techniques in overcoming children's aggressive behavior. This research employs a qualitative approach with a case study design, using observation, interviews, and documentation as data collection techniques. Data were analyzed using pattern matching, explanation building, and time-series analysis. The results indicate that the client was able to identify sources of anger, express emotions in a more controlled manner, and adopt more adaptive alternative behaviors when facing situations that trigger aggression. In addition, the client's daily interactions showed increased patience, improved listening skills, and reduced intensity of conflict with others. These findings are consistent with previous studies confirming the effectiveness of role play and play therapy techniques: in both individual and group settings for reducing aggressive behavior among children and adolescents.